2009
DOI: 10.1186/1471-2458-9-286
|View full text |Cite
|
Sign up to set email alerts
|

Over-indebtedness as a marker of socioeconomic status and its association with obesity: a cross-sectional study

Abstract: BackgroundThe recent credit crunch will have implications for private households. Low socioeconomic status is associated to various diseases. While income, education and occupational status is frequently used in definitions of socioeconomic status, over-indebtedness of private households is usually not considered. Over-indebtedness is currently increasing in high-income countries. However, its association with health – particularly with obesity – remains unknown. Therefore, the aim of this study was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 25 publications
3
53
0
2
Order By: Relevance
“…A small literature extends the aforementioned research to examine the relationship between health and debt. Münster et al (2009) find that over-indebtedness in Germany is negatively associated with physical health. Evidence also suggests that debt can result in a decline in physical health due to socio-economic hardship and material deprivation (Cohen et al, 2007;Reading & Reynolds, 2001).…”
Section: Literature Reviewmentioning
confidence: 75%
“…A small literature extends the aforementioned research to examine the relationship between health and debt. Münster et al (2009) find that over-indebtedness in Germany is negatively associated with physical health. Evidence also suggests that debt can result in a decline in physical health due to socio-economic hardship and material deprivation (Cohen et al, 2007;Reading & Reynolds, 2001).…”
Section: Literature Reviewmentioning
confidence: 75%
“…According to Puhl & Peterson (99), weight stigmatization and discrimination are particularly pronounced in the workplace setting. Their conclusions are supported by evidence that shows how obese individuals face stigma and prejudice at many stages of the employment process, including hiring, wage determination, and job promotions (74,103,105). Intentional efforts to focus on respect may address stigma and reflect a reasonable approach to appreciate human-centered cultures.…”
Section: Ethics Trust Respect and Human-centered Culturesmentioning
confidence: 94%
“…Four studies examined the health of those undergoing debt counselling; these are shown in appendix F. Two cohort studies compared over-indebted clients to the general population, finding an increased likelihood being overweight and reporting back pain after controlling for confounds (Munster, Ruger, Ochsmann, Letzel, & Toschke, 2009;Ochsmann, Rueger, Letzel, Drexler, & Muenster, 2009). O"Neill, Sorhaindo, Xiao, and Garman (2005) found that self-rated health was linked to reduced debts after a debt management intervention.…”
Section: Debt Management Clientsmentioning
confidence: 99%